METHODOLOGY OF USING THE VENN DIAGRAM AND THE INTEGRATION OF NATURAL SCIENCES IN TEACHING STUDENTS NITROGEN-CONTAINING ORGANIC COMPOUNDS - Kenjabayeva Xosiyat Ravshanbekovna; Shernazarov Iskandar Ergashovich (Bright Mind Publishing, 2025)
This article focuses on developing a methodology for using the Venn diagram and integrating natural sciences in teaching nitrogen-containing organic compounds. Today, an interdisciplinary integration approach is becoming important for enriching students' theoretical knowledge with practical skills, for an exciting and effective educational process. The article presents a developed method used in a generalized lesson plan so that students can better understand the structure, properties, and biological significance of nitrogen-containing organic compounds in an organic chemistry course, combining biology, physics, and ecology with the Venn diagram in teaching nitrogen-containing organic compounds.
Keywords: Containing nitrogen-containing organic compounds, integration of natural sciences, teaching methodology, integration of biology and chemistry, interdisciplinary approach in education, integration of theoretical and practical knowledge, integrated lesson plans, interactive teaching methods.